Essential oils of Calamintha nepeta, Origanum vulgare and Thymus mastichina of Alentejo (Portugal): a pharmacological approach - Arantes, Sílvia M. (2019)
Alentejo, in the south of Portugal, is rich in endemic aromatic plants, that are used as condiments and food additives by the local population. The aim of this study was to evaluate the antioxidant, antimicrobial and antiproliferative activities of EOs of autochthones Calamintha nepeta (L.) Savi (syn. Clinopodium nepeta (L.) Kuntze), Origanum vulgare L., and Thymus mastichina L. EOs were extracted from the aerial part of the plants by hydrodistillation and the chemical composition was analyzed by GC-FID and GC-MS. Antioxidant potential of the oils was evaluated by three different assays: DPPH radical, β-carotene/linoleic acid and reducing power methods. Antimicrobial activity of the oils was evaluated by a solid disk diffusion assay and minimal inhibitory concentrations (MIC) were determined by a microdilution broth method. Toxicity of the EOs was screened by the brine shrimp lethality test (LC50) and the oral lethal doses (DL50) were determined for mice. Cell viability was assessed by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay using MDAMB231 breast cancer cells.